A sensitive acoustic sensor using fiber bragg grating based on strain compensation - Awang, Noor Azura; Abdullah, S. N. A.; Yuzaile, Y. R.; N Mahmud, Nik N.H.E.; Zakaria, Z. (Institute of Advanced Scientific Research, 2020)
An acoustic sensitivity single ring fiber sensor with enhanced pressure sensitivity is designed by using Fiber Bragg Grating (FBG). Measurement sensitivity of the this fiber sensor is 0.3714 με/Hz. This sensor exhibited a good acoustic sensitivity, showing that the sensor has good sensing properties for the detection of the acoustic signals.